Trace Detection and Quantitation of Antibiotics in a South African Stream Receiving Wastewater Effluents and Municipal Dumpsite Leachates - Ncube, Somandla; Nuapia, Yannick Belo; Chimuka, Luke; Madikizela, Lawrence Mzukisi; Etale, Anita (Frontiers in Environmental Science, 2021)
One of the major concerns in the consumption of antibiotics is the discovery of antibacterial resistant genes due to prolonged exposure which makes their presence in environmental samples a priority. In this study, we have screened 52 antibiotics along a stream polluted with wastewater effluents and municipal dumpsite leachates. Of these antibiotics, 15 were detected in the stream while 3 sulfonamides (sulfamethizole, sulfamethazine, sulfamethoxazole), a fluoroquinolone (flumequine) and a diaminopyrimidine (trimethoprim) were further quantified. The concentrations of sulfamethizole, sulfamethazine, sulfamethoxazole ranged from not detected to 0.133 µg L-1, flumequine ranged from 0.222 to 0.686 µg L-1, while trimethoprim was up to 0.0618 µg L-1. The highest concentrations were recorded at the point source discharge with most antibiotics not detected further downstream. The current study has further confirmed wastewater effluents and dumpsite leachates as pathways of antibiotics into the environment. Only the persistent unsanctioned antibiotic, flumequine had its risk quotient above 0.1 making it an antibiotic of environmental concern. Multiresidue studies are still limited in Africa and the current study offers a platform for a research paradigm shift with more studies expected to emerge providing an improved overview of the release of antibiotics and other pharmaceuticals into Africa’s vulnerable surface water systems.